1992
DOI: 10.1177/030098589202900402
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Thyroid Structure and Function in Sprague-Dawley Rats

Abstract: Investigation of thyroid glands from 500 male and 500 female Sprague-Dawley rats, at time points of 8, 17, 30, 56, and 108 weeks of toxicity studies conducted at the Huntingdon Research Centre between 1981 and 1984, revealed age-related structural and functional changes that have previously not been well documented. The number of ultimobranchial cysts decreased with age, while area(s) of C-cell hyperplasia appeared with age. Beginning at 56 weeks, some of the thyroid follicles were hyperdistended with colloid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 20 publications
7
20
0
Order By: Relevance
“…We suppose that this noticeable difference in response to chronic EDP treatment between the central and peripheral follicles increased with advancing age, mostly due to exclusion of the peripheral follicles from active function in thyroid hormone synthesis and secretion. This assumption is consistent with a previous description of age-related changes in morphology of aged rat thyroid glands [24], as well as with the finding that old mouse thyroid contained a great number of ‘cold’, enlarged, distended follicles, that had lost their normal capacity to iodinate thyroglobulin and to respond to TSH [25, 26]. …”
Section: Discussionsupporting
confidence: 92%
“…We suppose that this noticeable difference in response to chronic EDP treatment between the central and peripheral follicles increased with advancing age, mostly due to exclusion of the peripheral follicles from active function in thyroid hormone synthesis and secretion. This assumption is consistent with a previous description of age-related changes in morphology of aged rat thyroid glands [24], as well as with the finding that old mouse thyroid contained a great number of ‘cold’, enlarged, distended follicles, that had lost their normal capacity to iodinate thyroglobulin and to respond to TSH [25, 26]. …”
Section: Discussionsupporting
confidence: 92%
“…Thyroid tissue of SO rats was characterized by the presence of inactive follicles, distended with dense colloid. Rao-Rupanagudi et al (1992) and other researchers (Cizza et al 1992, Mariotti et al 1995 also reported similar histological changes and progressive loss of follicular tissue with advancing age in the thyroid of male Sprague-Dawley or Fisher rats respectively with significant decreases in free serum TH levels. At the ultrastructural level, both in SO and in Orx middleaged rats, besides numerous follicular cells with typical organization of cell organelles, quite a few thyrocytes were characterized by dilated and distended RER cisternae.…”
Section: Discussionsupporting
confidence: 56%
“…The decrease in the T3 and T4 levels is the direct outcome of the decrease in the follicular cell number. The degenerative changes of the thyroid gland of aged Sprague-Dawley rats with concomitant decrease in the glandular function were reported earlier [6]. On the contrary, serum level of TSH exhibited a significant increase in the late adult control and senile rats.…”
Section: Discussionsupporting
confidence: 65%
“…Connective tissue could replace destroyed structures and degenerated follicles that more often occur in aging [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation